Analysis of Dynamic Flow Loss of High Water-Based Emulsion Pump - Lirong Wan; Yuang Yin; Zhiyuan Sun; Gaozuo Sun; Guoqing Qi; Ruwei Zhang (Actuators)
The emulsion pump’s flow loss directly affects its performance and efficiency. However, the annular plunger chamber leakage and valve core hysteresis are challenging to avoid during operation. This study systematically investigated the impact of the annular gap in the plunger cavity on emulsion pump performance. Using theoretical analysis and computational fluid dynamics methods, it explored the mechanism of the port valve hysteresis during discharge. The simulation results show that the leakage of the annular gap is proportional to the gap thickness and the inlet pressure and inversely proportional to the dynamic viscosity of the emulsion. With the increase of plunger eccentricity, the leakage increases slowly. The increase in the outlet diameter of the port valve will lead to more significant hysteresis of the valve core. The change of outlet pressure has little effect on the hysteresis and flow of the spool, and the response speed of the wing-guided bevel discharge valve is faster than that of the ordinary poppet valve. Considering the above factors, the flow distribution process of the emulsion pump can be accurately analyzed, providing a reference for pump optimization.